The attitude of the poet and scientist toward nature - Lyman, Gertrude M. (My University, 1897)
Introduction: As for untruths in poetry, poets are apt to go beyond the true facts in the case, and as a result, things are stated which are not in accordance with scientific laws. In taking up the different ways in which a few of the best poets have treated Nature we may have some idea of the elements in Nature poetry. Chaucer, who has been called “The Morning Star of English Song”, is said to have loved Nature equally as well as any poet but with that simple child-like love. Shakespeare, through all his dramas, forcibly impresses the reader with not only the characters of the persons but with it gives you and often-times by just a line or two a perfect picture of the surrounding scenery. In this he differs from our modern poets for in describing his characters he strikes off the surroundings most natural to fit the case, while the modern poet is prone to premeditate on all the scenery and then bring in the character later. For this reason Shakespeare excelled as a poet. Wordsworth is one of our very best Nature poets. While but a mere boy he had that love of Nature which grew up with him and made him the great interpreter of Nature. While roaming over the hills with other boys he had such beautiful thoughts which found expression later in his poems.
Citation: Lyman, Gertrude M. The attitude of the poet and scientist toward nature. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Poetry; Literature; Nature; Scientist; Theses; Manuscripts (documents)